Tracheostomy at a tertiary level hospital in Bangladesh: any change in pattern? - Talukdar, Debesh Chandra; Mahamud, Mashuque; Mahmud, Sharfuddin; Islam, Md Shaikhul; Akaiduzzaman, DGM; Litu, Manilal Aich; Biswas, Dipali (Journal of Dhaka Medical College, 2017)
Objective: This study was conducted on tracheostomy to find out the different indications and complications occured at the tertiary level hospital in Bangladesh. Study design: Cross-sectional observational study. Place and Duration: This study was conducted at the department of Otolaryngology & Head Neck surgery and department of ICU, Sir Salimullah Medical College Mitford Hospital, Dhaka & DMCH over one year from January 2014 to December 2014. Methodology: 55 tracheostomy operation were performed in both genders and all age groups either in emergency situations or within an elective environment. All the patients were registered with a definite protocol by filling a pre designed proforma equipped with demographic data, details of present illness mirroring the indication for the procedure, relevant physical examination & investigations, details of the surgical procedure of tracheostomy and postoperative follow up with note of any attendant complications described as immediate, early and late postoperative. Results: Mean age of this study was 40.09 years and male female ratio iwas 3.2: 1. 30(54.54%) patients underwent emergency tracheostomy and 25(45.46%) underwent tracheostomy electively. The commonest indications were laryngeal & hypopharyngeal malignancies which affected 28(50.9%) patients. The overall rate of complications was 25.45%. These were 4(28.57%) immediate post operative, 8(57.14%) early post operative and 2(3.63%) late post operative. Out of overall 14 complications, 11(36.66%) complications occurred in 40 patients who underwent tracheostomy in emergency and 3(12%) complications occurred in 25 patients who underwent tracheostomy electively. Conclusion: Upper airway obstruction due to laryngeal and hypopharyngal carcinoma still remains the most common indication for tracheostomy in our centre but prolonged intubation as an indication for tracheostomy is evolving based on recent improvement in the facilities available at our ICU. J Dhaka Medical College, Vol. 25, No.1, April, 2016, Page 67-71